Virulence of Cryptococcus sp. Biofilms In Vitro and In Vivo using Galleria mellonella as an Alternative Model - Benaducci, Tatiane; Sardi, Janaina de C. O.; Lourencetti, Natalia M. S.; Scorzoni, Liliana; Gullo, Fernanda P.; Rossi, Suélen A.; Derissi, Jaqueline B.; de Azevedo Prata, Márcia C.; Fusco-Almeida, Ana M.; Mendes-Giannini, Maria J. S. (Frontiers in Microbiology, 2016)
Cryptococcus neoformans and Cryptococcus gattii are fungal pathogens that are most commonly found in infections of the central nervous system, which cause life-threatening meningoencephalitis and can grow as a biofilm. Biofilms are structures conferring protection and resistance of microorganism to the antifungal drugs. This study compared the virulence of planktonic and biofilm cells of C. neoformans and C. gattii in Galleria mellonella model, as well as, the quantification of gene transcripts LAC1, URE1 and CAP59 by real time PCR. All three of the genes showed significantly increased expressions in the biofilm conditions for two species of Cryptococcus, when compared to planktonic cells. C. neoformans and C. gattii cells in the biofilm forms were more virulent than the planktonic cells in G. mellonella. This suggests that the biofilm conditions may contribute to the virulence profile. Our results contribute to a better understanding of the agents of cryptococcosis in the host-yeast aspects of the interaction.